The relationship of motivational characteristics to perceptions of written corrective feedback on essays among regular class students of Iloilo National High School - Paulino, Rex S (2018.)
This study sought to investigate the relationship of motivational characteristics (SMC) to perceptions of written corrective feedback (WCF) on essays among Regular Class students of Iloilo National High School for SY 2017-2018. Towo hundred forty0five (245) students were randomly selected in a probability sampling determined through Cochran?s sample size formula, corrected for finite population. As a cross-sectional survey study, a hybrid questionnaire of Johnstun (2008), Montgomery and Baker (2007), and Waller (2015) was made, pilot tested, and analyzed using the Cronbach alpha analysis (α=0897). Statistical analyses used were the Pearson Chi Square and Phi and Cramer?s V to further explore the relationship of results. Generally, students in the Regular Class have spectrum of incremental (x=4; x=5) and entity writing intelligences (x=3). Results showed significant relationships among the variables of SMC and WCF on essays. More motivated students thought more carefully about their teachers? WCF during the first drafts of their essays (p<0.005). During the final drafts, students observed that teachers focus more on content and mechanics in their compositions (p<.013). Moreover, students preferred that teachers correct most, if not, all of their errors both in the first (p<.000) and final drafts (p<.000). in correcting errors, more motivated students want teachers to underline or encircle some, if not, all their errors in first drafts through the use of correction codes (p<.002). These students were able to follow and understand their teachers? markings (p<.003). Students also believe that these marking symbols are helpful in correcting their errors (p<.002) and, most importantly, they will not commit the same errors on a new assignment after their teachers have corrected such errors (p<.000). Results validate a grassroots approach in determining the motivational characteristics of learners which greatly affect their success in learning a second language especially in writing.
Special Problem (Graduate, Master of Education in English as a Second Language) Division of Professional Education, College of Arts and Sciences
Keywords: Written corrective feedback -- Research